Bacterial community characteristics in the rhizosphere of Suaeda glauca versus bulk soil in coastal silt soil modified by sea-sand and their implications - An, Xiaochi; Wang, Zaifeng; Jiao, Kairui; Teng, Xiaoming; Zhou, Ruirong; Xu, Min; Lian, Bin (Frontiers in Marine Science, 2023)
In the exploitation and development of the muddy coastal zone in Lianyun New Town, Jiangsu Province, much coastal silt soil (CSS) has been formed through reclamation projects, which is difficult to use. The proportion of wild Suaeda glauca increased significantly and became a dominant species in CSS modified by sea-sand mulching (Treated CSS, TCSS), but it was still affected by saline-alkali stress. To use S. glauca efficiently to improve TCSS, high-throughput sequencing technology and conventional soil analysis methods were adopted to investigate the rhizosphere microbial community structure of S. glauca and the physico-chemical properties of TCSS as well as its internal correlation. The results showed that TCSS had low organic matter content, poor nutrients such as N and P, and poor fertility retention. TCSS was still affected by mild or moderate saline-alkali stress, and the total Ca was greater than 1%, so that the soil properties indicated a calcareous saline-alkali soil. The growth of S. glauca can reduce soil salinity and increase soil TN content, and its rhizosphere bacterial community was significantly different from that of bulk soil without S. glauca: the rhizosphere was significantly enriched with C-cycle-related bacterium such as organic matter degrading bacteria mariniflexile, photobacterium Sphingomonadaceae, and N-cycle-related bacterium such as nitrogen-fixing bacteria Azoarcus, denitrifying bacteria Pseudomonadaceae; the symbiotic relationship of rhizosphere bacterial community in S. glauca tended to be more complicated, and the functions of nitrogen-respiration, photo-nutrition, and methyl-nutrition were enhanced. Based on the above results, it is reasonable to predict that the interaction between S. glauca and its rhizosphere bacteria in TCSS could promote the process of soil carbon and nitrogen cycles, as to accelerate soil substance transformation and increase soil fertility, thus driving the benign development of TCSS. The results lay a theoretical basis for developing muddy coasts and promoting the precise improvement of TCSS by large-scale cultivation of S. glauca in the local area.